If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(1-5n)=-2(-6+6n)
We move all terms to the left:
3(1-5n)-(-2(-6+6n))=0
We add all the numbers together, and all the variables
3(-5n+1)-(-2(6n-6))=0
We multiply parentheses
-15n-(-2(6n-6))+3=0
We calculate terms in parentheses: -(-2(6n-6)), so:We get rid of parentheses
-2(6n-6)
We multiply parentheses
-12n+12
Back to the equation:
-(-12n+12)
-15n+12n-12+3=0
We add all the numbers together, and all the variables
-3n-9=0
We move all terms containing n to the left, all other terms to the right
-3n=9
n=9/-3
n=-3
| -6+m=3.6 | | 18-5c=-3(c+2) | | 2w^2+w-99=0 | | 25z+7z^2=12 | | 15+0.50m=25m | | 15+2(x)=21 | | 56t-30=11t-5 | | 4/9-7x=-7x+8/9 | | 3(k+6)=k+14 | | 2s-10=2s-10 | | 6x+7=8x−15 | | -5(4r+2)=90 | | (1/2)x+12=75 | | x(2x+3)=9x+15+x | | k/9+-1=10 | | -40=8x-8 | | 6(x-6)+6=8x-12X= | | 9X+X-5X=5x6 | | 7=x-8/3+8 | | 22h+16=8h+72 | | -2(7g)=30 | | y+7(-2)=10 | | t-4.25=-4 | | 3x-30=15-2x | | 4x-6+4x-2=32 | | x(2)=9/100 | | (5x+6)-2(x-1)=3 | | 5x-3/2=x-5 | | x/1.5=16 | | 5x4-10x3-2x2=0 | | F(x)=-3x+15 | | 5x+9=5x+1 |